Intangible Assets in Cross-border Business Restructurings Within the EU : Tax Incentives in Location Choices - Lepistö, Jonna (My University, 2020)
Multinational entities have many possibilities to utilise the global tax scheme by rearranging their business activities internally within the global entity. An increasing parts of value of the nowadays MNEs intra-group transactions are obtained particularly from intellectual property rights transfers and utilisation. An intangible’s location can easily be changed from its operational location to a central location, where it becomes subject to another tax jurisdiction and, therefore, intellectual property rights are often seen as a facilitators for MNEs’ global profit shifting. As intangibles do not have a physical form, transfers do not require anything other than contractual restructurings. The location choice may produce significant tax benefits for the MNE via lower foreign tax rates when companies transfer their intangible assets particularly to low-tax jurisdictions. The research examines cross-border business restructuring of intellectual property rights from the assets location choice perspective. The aim of the research is to find out whether tax incentives are affecting MNEs intangible restructuring decisions within the EU and, in particular, the intangibles’ location choices. Additionally, the research assesses the kinds of tax incentives affecting the intangibles’ location choices. The research question is supported by an analysis of the intangible restructuring phenomenon on a general level, where ownership and valuation issues are taken into consideration. The research is based on legal dogmatic research methodology. The topic is interpreted with the help of current legislation, the OECD guidelines and academic articles and books. The findings indicate that the intangibles’ location choice is in many ways interrelated to tax incentives, and multinational entities often make intangible restructuring and location considerations in order to impact their tax burden.